2015
DOI: 10.1364/oe.23.023287
|View full text |Cite
|
Sign up to set email alerts
|

Temporal mode sorting using dual-stage quantum frequency conversion by asymmetric Bragg scattering

Abstract: . Temporal mode sorting using dual-stage quantum frequency conversion by asymmetric Bragg scattering. Optics Express, 23(18) Abstract:The temporal shape of single photons provides a highdimensional basis of temporal modes, and can therefore support quantum computing schemes that go beyond the qubit. However, the lack of linear optical components to act as quantum gates has made it challenging to efficiently address specific temporal-mode components from an arbitrary superposition. Recent progress towards real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It has previously been shown that perfect selectivity cannot be achieved in simple inter-pulse interaction systems due to time-ordering corrections [37]. But selectivity asymptotically approaching 100% can be achieved in cascaded, multi-stage FC implementations [37][38][39]48]. This paper does not address multi-stage FC.…”
Section: Equations Of Motion and Selectivitymentioning
confidence: 97%
See 1 more Smart Citation
“…It has previously been shown that perfect selectivity cannot be achieved in simple inter-pulse interaction systems due to time-ordering corrections [37]. But selectivity asymptotically approaching 100% can be achieved in cascaded, multi-stage FC implementations [37][38][39]48]. This paper does not address multi-stage FC.…”
Section: Equations Of Motion and Selectivitymentioning
confidence: 97%
“…The Green function solutions for the GVM regime are known in closed analytical form [36,44], which aids in numerical analysis, as well as physical system design. We have validated these analytical solutions using regime-agnostic wave-mixing simulations based on a numerical splitstep implementation of the propagation and interaction of the various fields [36,38,39,48]. Specifically, we propagate the fields and apply dispersion in the Fourier domain, and "mix" them using fourth-order Runge-Kutta in the time domain, alternating between the two for every iteration.…”
Section: Group-velocity Matched Regimementioning
confidence: 99%
“…FWM in single-mode fibers has already been researched for many different applications within the quantum communication sciences, including frequency conversion of quantum states [9], sorting and shaping of temporal modes [10], generation of temporally uncorrelated pure single-photon states [11], and two-temporal-mode photon states by vector FWM [12]. However, the application of single-mode FWM poses significant challenges, such as spontaneous Raman scattering [13] and phase matching, which is constrained by group-velocity dispersion [14].…”
Section: Introductionmentioning
confidence: 99%
“…This purification can be achieved by spectrally filtering out the correlated parts of the joint signal-idler spectrum [13], or by sophisticated methods such as temporal-mode matched filtering [14] or mode-sensitive frequency conversion [15,16]. However, all of these methods share a common downside in that they result in additional photon losses and, consequently, lead to lower * jesbch@fotonik.dtu.dk single-photon rates.…”
Section: Introductionmentioning
confidence: 99%